PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 5E DENGAN METODE PEMBERIAN TUGAS DAN RESITASI UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA PADA POKOK BAHASAN ARITMETIKA SOSIAL SISWA KELAS VII A SEMESTER GENAP SMP NEGERI 10 JEMBER TAHUN AJARAN 2 - Lestari, Eka Cahya; Hobri, H; Kristiana, Arika Indah (Department of Mathematics Education , University of Jember, 2015)
Abstract.The purpose of this research is to increase student’s activities and learning achievement score. The research implemented Learning Cycle 5E model with giving assignment and recitation methods. This research type is a Classroom Actions Research (CAR) of two cycles, there are two classes in each cycle. The topic in the research is a social arithmetic. The research methods are observation, test, interview, and documentation. The data analysis in this research are student’s activities, student’s achievement score and teacher’s activities. The research show that the student activities for spiritual attitude attaine 65,28% and for social attitude attaine 68,55% in the first cycles and the student activities for spiritual attitude attaine 95,14% and for social attitude attaine 78,25% in the second cycles. The teacher’s activities attaine 85,19% in the first cycles and 96,30% in the second cycles, and the achievement score attaine 55,56% in the first cycles and 80,56% in the second cycles. It can be concluded that the implementation of Learning Cycle 5E model with giving assignment and recitation methods is able to improve student’s activities and learning outcome. Key Words : Learning Cycle 5E model with giving assignment and recitation methods, Social Arithmetic, student’s result study, student’s activities.